Sharing economy on election campaign through social media - Widhiasthini, Ni Wayan (International research journal of management, IT and social sciences, 2020)
Simultaneous regional head elections in 2020 are a democratic party held during the Covid19 pandemic. There are social restrictions and community mobility and in the context of preventing the spread of the virus, social media has become the main choice for election participants in campaigning. The sharing economy is the reference in this article, based on the prevailing view in society that elections are more closely watched from the political aspect. The era of disruption has penetrated various fields including politics, democracy, especially in the administration of elections. The problem in this article describes the practice of sharing the economy of the election campaign through social media. The goal to be achieved is to contribute to thoughts and to provide awareness that campaigns on social media are not merely political activities. But economic activity with a collaborative economic concept. The discussion of this article covers the six districts in Bali that are participating in the general election simultaneously in 2020. The results of the discussion show that the practice of sharing economy in the election campaign through social media is carried out through the selection of the social media platform that will be used to carry out the campaign.